Preparation method of functionalized light-driven nano-motor adsorbent and adsorption application of functionalized light-driven nano-motor adsorbent

By modifying dithiosuccinic acid and gold-loaded nanoparticles on Elosite nanotubes, a near-infrared light-driven nanomotor adsorbent was prepared, which solved the problems of biocompatibility and low adsorption efficiency of blood perfusion adsorbents, and achieved It efficiently removes lead ions in the blood and is suitable for biomedical applications.

CN119318947AActive Publication Date: 2025-01-17JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411490582.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-17
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The poor biocompatibility and low adsorption efficiency of existing blood perfusion adsorbents lead to low removal efficiency of lead ions and low mass transfer efficiency, making it difficult to meet environmental protection and biomedical needs.

Method used

Elosite nanotube (HNTs)-based photothermal nanomotor adsorbent modified with dimercaptosuccinic acid (DMSA) improves the adsorption performance and biocompatibility of the adsorbent through near-infrared light driving, and enhances the selection of lead ions sexual adsorption.

Benefits of technology

The lead ion removal efficiency is achieved above 90%, which significantly improves the adsorption capacity and mass transfer efficiency, and has excellent biocompatibility and selectivity, which is suitable for biological environment applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318947A_ABST
    Figure CN119318947A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of ion identification, adsorption and separation functional materials, and discloses a preparation method and adsorption application of a functionalized light-driven nano motor adsorbent. The gold nanoparticles Au NPs are loaded in the HNTs by adopting a solvent method so as to generate a good photothermal effect, and then the surface is covered with the PDA layer and the DMSA, so that the adsorption performance of the adsorbent is improved. Experiments show that the Au-coated DHNTs-DMSA has good photothermal conversion efficiency, biocompatibility and biological safety, and the in-vitro blood lead removal rate is as high as 91.25%, so that the Au-coated DHNTs-DMSA can be used for effectively treating lead poisoning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of functional materials for ion recognition, adsorption and separation, and specifically relates to a preparation method of a functionalized light-driven nanomotor adsorbent and its adsorption application. Technical Background

[0002] Lead is a heavy metal widely used in various industrial productions. However, the lead discharged from industrial production will cause serious pollution to the environment. In addition, the lead in the environment can easily enter the human bones, blood and other soft tissues through the food chain and gradually accumulate in the human body, causing serious damage to the nervous, kidney, cardiovascular and reproductive systems. Therefore, how to effectively remove lead from the blood has become a major problem in the field of environmental protection and biomedical functional materials. At present. Hemoperfusion is one of the most commonly used methods to remove lead ions from the blood. It has the advantages of large adsorption capacity and wide adaptability, but the biocompatibility of traditional hemoperfusion adsorbents is poor, and the selectivity for the target is low, and the removal efficiency and application environment are relatively limited. Therefore, it is urgent to develop new hemoperfusion adsorbents with high safety and good biocompatibility. Halloysite nanotubes (HNTs), as natural clay minerals, have the advantages of low cost, large specific surface area and good biocompatibility. They are often used in the field of drug transportation. Therefore, introducing HNTs as a base material into the preparation of new hemoperfusion adsorbents can greatly improve the safety and biocompatibility of the adsorbent. However, this is not enough, because the adsorption efficiency of the adsorbent is low due to its low mass transfer efficiency, which will prolong the time of removing blood lead. Therefore, the development of a hemoperfusion adsorbent with high adsorption efficiency is still an urgent problem to be solved.

[0003] In order to further enhance the adsorption performance of the new blood perfusion adsorbent, we combined the strategy of micro / nanomotors to prepare micro / nanomotor adsorbents and used them to solve the problem of rapid contact between the adsorbent and the target. Artificial micro / nanomotors have the characteristics of converting various external energies into kinetic energy and are widely used in biomedical fields such as drug delivery, medical diagnosis and chemical detoxification. The main sources of external energy include various stimuli such as light, electric field, magnetic field, temperature and fuel gradient, which can trigger the propulsion, stop and change of direction of the motor. Most of the micro / nanomotors are driven by decomposition matrix, but in actual application environments, toxic chemical fuels such as hydrogen peroxide or hydrazine are often required, which seriously limits the application of micro / nanomotors in biomedicine. Near-infrared light (NIR) is an electromagnetic wave between visible light and mid-infrared light. It has the advantages of high penetration, good controllability, good safety, significant thermal effect and remote transmission. Therefore, NIR-driven photothermal motors are more suitable for realizing controllable motion behavior in complex biological environments. In summary, the present invention intends to combine HNTs and NIR-driven photothermal motors to prepare a new type of hemoperfusion adsorbent with high safety, good biocompatibility and excellent adsorption performance. This idea has not been reported yet. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a functionalized light-driven nanomotor adsorbent to selectively adsorb and separate Pb(II) in order to solve the technical bottlenecks such as low adsorption performance, poor biocompatibility, and application conditions that are not suitable for biological environments of existing nanoadsorbents.

[0005] The present invention prepares a HNTs-based photothermal nanomotor adsorbent modified with dithiosuccinic acid (DMSA) to remove lead ions from blood. First, gold nanoparticles are loaded on the inner surface of HNTs by solvent evaporation, and then polydopamine (PDA) and DMSA are modified on the outer surface to obtain Au@DHNTs-DMSA nanomotor adsorbent. And through near-infrared test experiments, it is shown that Au@DHNTs-DMSA will quickly generate heat under near-infrared light and form a thermal gradient on the surface, and has good photothermal conversion efficiency. And under NIR irradiation, the motion behavior is realized, the mass transfer efficiency between the adsorbent and Pb(II) is improved, and the ambient temperature during adsorption is also increased, significantly improving the adsorption capacity. At the same time, as a blood lead adsorbent, Au@DHNTs-DMSA has good biocompatibility, and the removal efficiency of blood lead is also higher than 90%. In the selectivity experiment, it was found that Au@DHNTs-DMSA hardly adsorbed other ions in simulated blood when adsorbing Pb(II), and had excellent adsorption selectivity.

[0006] In order to achieve the above technical purpose, the technical solution adopted by the present invention is:

[0007] The present invention proposes a method for preparing a functionalized light-driven nanomotor adsorbent (Au@DHNTs-DMSA), simulates a Pb(II) solution, and evaluates the adsorption performance of the Au@DHNTs-DMSA adsorbent for selectively adsorbing and separating Pb(II) ions. The method comprises the following steps:

[0008] (1) Activation of Halloysite Nanotubes (HNTs)

[0009] The HNTs powder is dispersed in a hydrochloric acid solution, stirred for a certain period of time at room temperature, and then the HNTs treated with centrifugal acid are washed with deionized water, and finally dried in a vacuum drying oven to obtain the activated HNTs;

[0010] (2) Halloysite nanotubes loaded with gold nanoparticles (Au@HNTs)

[0011] The HNTs activated in step (1) are mixed with HAuCl4·3H2O, ethanol, toluene, oleylamine and oleic acid, dispersed by ultrasonication, and heated and stirred for the first time under magnetic stirring;

[0012] Then, a certain amount of ascorbic acid AAc was added, and the mixture was heated and stirred for the second time. The obtained dark product was washed repeatedly with ethanol and toluene alternately for several times, and then washed with toluene for several times to remove the free gold nanoparticles Au NPS in the solution, and finally dried in a vacuum drying oven to obtain the product Au@HNTs;

[0013] (3) Preparation of Au@DHNTs-DMSA by surface modification of Au@HNTs with polydopamine and DMSA

[0014] Au@HNTs were dispersed in Tris buffer, and then mixed evenly with Tris buffer containing dopamine hydrochloride (DA) and dithiothreitol succinic acid (DMSA). After stirring at a certain temperature for a certain time, the solid product was centrifuged and washed with ethanol and deionized water, and finally dried in a vacuum drying oven to obtain Au@DHNTs-DMSA.

[0015] In step (1), the dosage ratio of the HNTs powder to the hydrochloric acid solution is: 1.0 g: (5.0-15) mL, wherein the concentration of the hydrochloric acid solution is 2.0 mol / L.

[0016] In step (1), the stirring time is 24 hours.

[0017] In step (1), the acid-treated HNTs are washed with deionized water until the pH of the solution is 7.0.

[0018] In step (2), the dosage ratio of the activated NHTs, HAuCl4·3H2O, ethanol, toluene, oleylamine, oleic acid and ascorbic acid (AAc) is 1.0 mg: (1.40-1.50) mg: (0.10-0.15) mL: (0.10-0.15) mL: (0.01-0.05) mL: (0.01-0.05) mL: (5.0-15) mg.

[0019] In step (2), the temperature of the first heating and stirring is 55° C. and the time is 1.0 min.

[0020] In step (2), the temperature of the second heating and stirring is 55° C. and the time is 20 min.

[0021] In step (3), the dosage ratio of Au@HNTs to Tris buffer containing dopamine hydrochloride (DA) and dithiothiosuccinic acid (DMSA) is 1.0 mg:(0.25-0.75) mL, wherein the concentrations of dopamine hydrochloride (DA) and dithiothiosuccinic acid (DMSA) in the Tris buffer containing dopamine hydrochloride (DA) and dithiothiosuccinic acid (DMSA) are both 2.0 mg / mL.

[0022] In step (3), the concentration of the Tris buffer is 10 mM, and the pH is 8.5.

[0023] In step (3), the stirring temperature is 37° C. and the stirring time is 12 h.

[0024] In steps (1), (2) and (3), the temperature of the vacuum drying oven is 50°C.

[0025] The Au@DHNTs-DMSA adsorbent prepared by the present invention is used for the selective adsorption and separation of Pb(II).

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] The present invention designs a blood lead adsorbent that is more suitable for biological environments. Au is loaded in HNTs and then DMSA is modified on the outer surface of HNTs by PDA to synthesize a near-infrared light-driven Au@DHNTs-DMSA nanomotor adsorbent. Due to the presence of thiol and carboxyl groups in DMSA, Au@DHNTs-DMSA has extremely high selectivity. At the same time, Au@DHNTs-DMSA also has good biocompatibility and biosafety, so it can effectively treat lead poisoning, which has important research significance for biological applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1FT-IR (a) and XRD (b) patterns of Au@DHNTs and Au@DHNTs-DMSA prepared in Example 1.

[0029] Figure 2 (a, b) are TEM images of Au@DHNTs (the mass of ascorbic acid is 150 mg) in Example 1.

[0030] (c) is the TEM image of Au@DHNTs (the mass of ascorbic acid is 75 mg) in Example 2.

[0031] (d)-(f) are TEM images of Au@DHNTs-DMSA in Example 1.

[0032] Figure 3 In Example 1, 1.0 W / cm 2 Thermal imaging of Au@DHNTs-DMSA suspensions of different concentrations under near-infrared light (808 nm) (a); Temperature changes of 1.0 mg / mL Au@DHNTs-DMSA suspension under near-infrared light (808 nm) of different powers (b).

[0033] Figure 4 Schematic diagram of the Au@DHNTs-DMSA near-infrared nanomotor prepared in Example 1 (a) and the motion trajectory (b) and average speed (c) of Au@DHNTs-DMSA under near-infrared irradiation of different powers.

[0034] Figure 5 The effects of pH value (a) and temperature (b) on the adsorption of Au@DHNTs-DMSA in Example 1, and the Van't Hoff diagram.

[0035] Figure 6 (a) and (b) the adsorption kinetics diagram of Au@DHNTs-DMSA prepared in Example 1 for Pb(II).

[0036] Figure 7 The adsorption capacity change curve of Au@DHNTs-DMSA prepared in Example 1 under the presence or absence of near-infrared light (NIR) irradiation.

[0037] Figure 8 (a) The selective adsorption graph of Au@DHNTs-DMSA prepared in Example 1 and (b) the removal rate of blood lead by Au@DHNTs-DMSA under near-infrared light. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with specific embodiments and drawings.

[0039] Embodiment 1:

[0040] (1) Activation of Halloysite Nanotubes (HNTs)

[0041] 5.0 g of HNTs powder was dispersed in 50 mL of hydrochloric acid solution (2.0 mol / L), stirred at room temperature for 24 h, and then the acid-treated HNTs were washed with deionized water until the solution reached pH = 7.0, and finally dried in a vacuum drying oven at 50° C. to obtain activated HNTs.

[0042] (2) Halloysite nanotubes loaded with gold nanoparticles (Au@HNTs)

[0043] 15 mg of activated HNTs, 22 mg of HAuCl4·3H2O, 2.0 mL of ethanol, 2.0 mL of toluene, 0.5 mL of oleylamine and 0.5 mL of oleic acid were added to a 20 mL flask and mixed and dispersed by ultrasonication. The mixture was heated to 55 °C under magnetic stirring and stirred for 1.0 min. Then 150 mg of ascorbic acid (AAc) was added to the flask and stirred at 55 °C for 20 min. At this time, the color of the solution quickly changed from light yellow to dark purple, indicating that gold nanoparticles (Au NPs) had been formed. The obtained dark product was washed repeatedly with ethanol and toluene alternately for several times, and then washed repeatedly with toluene for several times to remove the free Au NPs in the solution. Finally, the product was dried in a vacuum oven to obtain Au@HNTs.

[0044] (3) Preparation of Au@DHNTs-DMSA by surface modification of Au@HNTs with polydopamine and DMSA

[0045] 100 mg Au@HNTs were dispersed in Tris buffer (10 Mm, pH = 8.5), and then mixed with 50 mL Tris buffer containing 2.0 mg / mL dopamine hydrochloride (DA) and 2.0 mg / mL dithiothiosuccinic acid (DMSA). After stirring at 37 ° C for 12 h, the solid product was centrifuged and washed with ethanol and deionized water, and finally dried in a vacuum oven at 50 ° C to obtain Au@DHNTs-DMSA.

[0046] Embodiment 2:

[0047] (1) Activation of Halloysite Nanotubes (HNTs)

[0048] 5.0 g of HNTs powder was dispersed in 25 mL of hydrochloric acid solution (2.0 mol / L), stirred at room temperature for 24 h, and then the acid-treated HNTs were washed with deionized water until the solution reached pH = 7.0, and finally dried in a vacuum drying oven at 50 °C to obtain activated NHTs.

[0049] (2) Halloysite nanotubes loaded with gold nanoparticles (Au@HNTs)

[0050] 15 mg of activated HNTs, 21 mg of HAuCl4·3H2O, 1.5 mL of ethanol, 1.5 mL of toluene, 0.15 mL of oleylamine and 0.15 mL of oleic acid were added to a 20 mL flask and mixed and dispersed by ultrasonication. The mixture was heated to 55 °C under magnetic stirring and stirred for 1.0 min. Then 75 mg of ascorbic acid (AAc) was added to the flask and stirred at 55 °C for 20 min. At this time, the color of the solution quickly changed from light yellow to dark purple, indicating that gold nanoparticles (Au NPs) had been formed. The obtained dark product was washed repeatedly with ethanol and toluene alternately for several times, and then washed with toluene for several times to remove the free Au NPs in the solution. Finally, the product was dried in a vacuum oven to obtain Au@HNTs.

[0051] (3) Preparation of Au@DHNTs-DMSA by surface modification of Au@HNTs with polydopamine and DMSA

[0052] 100 mg Au@HNTs were dispersed in Tris buffer (10 Mm, pH = 8.5), and then mixed with 25 mL of Tris buffer containing 2.0 mg / mL dopamine hydrochloride (DA) and 2.0 mg / mL dithiothiosuccinic acid (DMSA). After stirring at 37 ° C for 12 h, the solid product was centrifuged and washed with ethanol and deionized water, and finally dried in a vacuum oven at 50 ° C to obtain Au@DHNTs-DMSA.

[0053] Embodiment 3:

[0054] (1) Activation of Halloysite Nanotubes (HNTs)

[0055] 5.0 g of HNTs powder was dispersed in 75 mL of hydrochloric acid solution (2.0 mol / L), stirred at room temperature for 24 h, and then the acid-treated HNTs were washed with deionized water until the solution reached pH = 7.0, and finally dried in a vacuum drying oven at 50 °C to obtain activated NHTs.

[0056] (2) Halloysite nanotubes loaded with gold nanoparticles (Au@HNTs)

[0057] 15 mg of activated NHTs, 22.5 mg of HAuCl4·3H2O, 2.25 mL of ethanol, 2.25 mL of toluene, 0.75 mL of oleylamine and 0.75 mL of oleic acid were added to a 20 mL flask and mixed and dispersed by ultrasonication. The mixture was heated to 55 °C under magnetic stirring and stirred for 1.0 min. Then 225 mg of ascorbic acid (AAc) was added to the flask and stirred at 55 °C for 20 min. At this time, the color of the solution quickly changed from light yellow to dark purple, which indicated that gold nanoparticles (Au NPs) had been formed. The obtained dark product was washed repeatedly with ethanol and toluene alternately for several times, and then washed with toluene for several times to remove the free Au NPS in the solution. Finally, the product was dried in a vacuum oven to obtain Au@HNTs.

[0058] (3) Preparation of Au@DHNTs-DMSA by surface modification of Au@HNTs with polydopamine and DMSA

[0059] 100 mg Au@HNTs were dispersed in Tris buffer (10 Mm, pH = 8.5), and then mixed with 75 mL Tris buffer containing 2.0 mg / mL dopamine hydrochloride (DA) and 2.0 mg / mL dithiothiosuccinic acid (DMSA). After stirring at 37 ° C for 12 h, the solid product was centrifuged and washed with ethanol and deionized water, and finally dried in a vacuum oven at 50 ° C to obtain Au@DHNTs-DMSA.

[0060] Figure 1 (a) shows the FT-IR spectra of Au@HNTs and Au@DHNTs-DMSA. As a metal element, AuNPs have no vibration peaks in the infrared spectrum, so the spectrum of Au@HNTs is consistent with that of HNTs. In the spectrum of Au@DHNTs-DMSA, at 3630 cm -1 and 3570cm -1 The characteristic peak at 1230 cm-1 is from the stretching vibration of Si-OH, but the intensity of the characteristic peak is reduced due to the modification of PDA and DMSA. -1 and 1400cm -1 The two characteristic peaks at 3346 cm are caused by the stretching vibration of C=O and the bending vibration of NH in PDA, while the -1 The broad peak at 1631 cm is attributed to the bending vibration of NH and OH. However, the infrared spectrum has a low detection sensitivity to -SH, so it is difficult to observe its absorption peak. -1 The characteristic peaks can be attributed to the stretching vibration of C=O in DMSA. According to the FTIR results, PDA and DMSA were successfully modified on the outer surface of HNTs. Figure 1The XRD results in (b) show that the spectra of Au@HNTs and Au@DHNTs-DMSA both contain the gold-specific (111), (200), (220) and (311) crystal planes, which proves that gold nanoparticles (AuNPs) are loaded on HNTs and that the AuNPs are not destroyed in the subsequent modification.

[0061] Figure 2 The morphology and nanoparticle structure of Au@HNTs and Au@DHNTs-DMSA were analyzed by transmission electron microscopy (TEM). Figure 2 As shown in (ac), different loading effects can be achieved by using different masses of ascorbic acid (AAc) to reduce gold tetrachloride when loading Au NPs. When the mass of AAc is 150 mg, the size of Au NPs in the obtained Au@HNTs is about 10-30 nm and is evenly distributed in the tube in a chain-like arrangement ( Figure 2 (a, b)), even Au NPs are linked to each other; when the AAc mass is 75 mg, Figure 2 In (c), it was observed that only a small amount of Au NPs was loaded in the Au NPs tube, indicating that 150 mg is more conducive to the preparation of motor adsorbents with good photosensitivity. Then, the Au@HNTs modified by PDA and DMSA maintained a hollow tubular structure, and the polymer was clearly seen on the outer surface. This is because the presence of the PDA layer makes the outer surface of Au@DHNTs-DMSA rough and uneven in thickness, as shown in Figure 2. Figure 2 (d-f), indicating that the surface modification was successful and the modification process did not affect the tubular structure of HNTs.

[0062] In the work, the photothermal conversion performance of Au@DHNTs-DMSA was tested by using a near-infrared laser emitter and an infrared thermal imager, providing a basis for the subsequent movement and adsorption process of the motor adsorbent. Figure 3 (a) is a thermal image of Au@DHNTs-DMSA suspension at different concentrations. It can be observed that under the irradiation of near-infrared light, the Au@DHNTs-DMSA suspension system has a very obvious temperature rise phenomenon compared with pure water, and the temperature rise gradient increases with the extension of irradiation time, which shows that it has excellent photothermal properties. Figure 3 As can be seen from (b), as the near-infrared light power increases, the temperature rises. 2 The highest temperature after 120s of illumination is 0.75W / cm 2 The high is 12.4℃.

[0063] Figure 4(a) is a schematic diagram of the near-infrared driven nanomotor. The PDA and Au NPs on the Au@DHNTs-DMSA can absorb near-infrared light, generate a temperature gradient, and drive through self-thermophoresis. Figure 4 As shown in (b), as the near-infrared light power density increases from 0.5 W / m 2 Increase to 1.0W / cm 2 At the same time, the trajectory of the nanomotor is extended, indicating that regulating the infrared light intensity can achieve control of the motor speed. At the same time, near-infrared light drive makes the movement of Au@DHNTs-DMSA directional, and its trajectory is close to a straight line. The motor trajectory is analyzed through the Tracking plug-in, and the calculated average speed can be used to quantitatively compare the propulsion performance of Au@DHNTs-DMSA under different near-infrared laser power densities. Figure 4 In (c), when the power density of near-infrared light increases from 0.5 W / cm 2 Increase to 1.0W / cm 2 When 1.0 W / cm2 was used, the average motion velocity of Au@DHNTs-DMSA increased from 194.6 μm / s to 327.3 μm / s, indicating that effective near-infrared light driving was achieved. 2 The near-infrared light-driven motor accelerates the mass transfer rate and increases the probability of Au@DHNTs-DMSA contacting lead ions, thereby improving the adsorption performance.

[0064] Test Example 1:

[0065] 8.0 mg of the product Au@DHNTs-DMSA of step (3) in Example 1 was added to a 10 mL centrifuge tube, followed by 8.0 mL of a 50 mg / L Pb(II) solution with pH values ​​of 1.0, 2.0, 3.0, 4.0, 5.0 and 6.0, and the centrifuge tube was placed in a constant temperature water bath for 12 h of static adsorption. After the adsorption was completed, the adsorbent was separated by centrifugation, and the supernatant was filtered using a microporous nitrocellulose membrane. The Pb(II) concentration in the filtrate was determined by ICP-OES. The above steps were performed in three sets of parallel experiments to calculate the equilibrium adsorption amount Q e (mg / g). Figure 5 As shown in (a), when the solution pH increases from 1.0 to 5.0, the adsorption capacity (Q e ) gradually increases, and when the pH is 5.0-6.0, Q e The adsorption capacity gradually stabilized and reached a maximum of 46.80 mg / g. This is because a large amount of H +It will compete with Pb(Ⅱ) for adsorption and will occupy most of the adsorption sites on the surface of Au@DHNTs-DMSA. As the pH value increases, Pb(Ⅱ) dominates the adsorption process. However, during the experiment, when pH>5.0, the Pb(Ⅱ) solution began to precipitate, which will affect the evaluation of the adsorption performance of Au@DHNTs-DMSA. Therefore, the following experiment selected pH=5.0 as the optimal adsorption condition to study the adsorption capacity of Au@DHNTs-DMSA for lead ions.

[0066] Test Example 2:

[0067] 8.0 mg of the product Au@DHNTs-DMSA of step (3) in Example 1 was added to 8.0 mL of Pb(II) solution (50 mg / L, pH=5.0) and adsorbed at 25°C, 35°C and 45°C for 1.0 h. The mixture was then filtered with a nitrocellulose membrane and the residual lead ion concentration of the supernatant was determined by ICP-OES. The above steps were performed in three parallel experiments to calculate the equilibrium adsorption amount Q e (mg / g). Figure 5 As shown in (b), when the temperature rises from 25°C to 45°C, the adsorption capacity of Au@DHNTs-DMSA increases from 46.677 mg / g to 49.734 mg / g. At the same time, the adsorption thermodynamic properties of the nanomotor adsorbent were studied using thermodynamic parameters, including Gibbs free energy (ΔG), enthalpy change (ΔH) and entropy change (ΔS), to determine the thermodynamic adsorption mechanism of Au@DHNTs-DMSA for Pb(Ⅱ). The Van't Hoff plot is ln(Q e / C e ) and 1 / T ( Figure 5 (c)) is used to calculate the ΔH, ΔS, and ΔG values. ΔH>0 indicates that the adsorption process of Pb(Ⅱ) by the nanomotor is an endothermic reaction, which means that the higher the temperature, the better the adsorption performance. In addition, ΔG<0 indicates that the adsorption process is a reversible spontaneous reaction, and the increase in temperature is conducive to the adsorption, which increases the adsorption capacity.

[0068] By studying the adsorption isotherm of the adsorbent, the adsorption characteristics of the adsorbent can be evaluated, which helps to understand the adsorption principle between the adsorbent and the target. Figure 6 As shown in (b), with the increase of the initial concentration of Pb(II), the adsorption capacity of Au@DHNTs-DMSA increased significantly and finally reached adsorption saturation. In this work, the Langmuir and Freundlich models were used to fit and analyze the equilibrium adsorption process. At different temperatures, the fitting coefficient R1 of the Langmuir model 2Both are higher than the Freundlich model, indicating that the Langmuir model can better describe the adsorption process, which is a monolayer adsorption and mainly depends on the chemical interaction between surface functional groups and lead ions.

[0069] Test Example 3:

[0070] 8.0 mg of the product Au@DHNTs-DMSA of step (3) in Example 1 was added to 8.0 mL of Pb(II) solution (50 mg / L, pH=5.0) and adsorbed at 25°C for 1.0 min, 3.0 min, 5.0 min, 10 min, 15 min, 20 min, 30 min and 40 min, respectively. The mixture was filtered with a nitrocellulose membrane and the residual lead ion concentration of the supernatant was determined by ICP-OES. The above steps were carried out in three parallel experiments and Q was calculated. t (mg / g). Figure 6 (a) shows the adsorption kinetics of Pb(Ⅱ) by the adsorbent (0-40min). The adsorption process can be roughly divided into three stages. In the initial stage (about 0-5.0min), the adsorption capacity increases rapidly, and in the transition stage (5.0-20min), the adsorption growth slows down significantly, and finally reaches the adsorption equilibrium stage (about 20-40min), and the active sites on the adsorbent reach saturation (Q e =46.129 mg / g). The adsorption kinetic data were fitted using pseudo-first-order kinetic model and pseudo-second-order kinetic model. The fitting coefficient R2 2 Compared with the R1 of the pseudo-first-order kinetic model 2 High, Q e,c With Q e,e This indicates that the pseudo-second-order kinetic model is applicable to the adsorption kinetics of Au@DHNTs-DMSA to Pb(Ⅱ), which is mainly chemical adsorption.

[0071] Test example 4:

[0072] Use 1.0W / cm 2 The product Au@DHNTs-DMSA of step (3) in Example 1 was driven to adsorb Pb(II) in aqueous solution (200 mg / L, pH=5.0) by near-infrared light irradiation of high power. The irradiation time was 0.5 min, 1.0 min, 2.0 min, 3.0 min, 4.0 min and 5.0 min. The residual Pb(II) concentration was measured by ICP-OES and the adsorption capacity (Q e , mg / g). Experimental data are as follows Figure 7As shown in the figure, with the increase of near-infrared light irradiation time, the adsorption capacity also increases significantly, and the adsorption capacity under near-infrared light irradiation at each time point is higher than the adsorption capacity without near-infrared light irradiation. The adsorption capacity of Au@DHNTs-DMSA for Pb(II) is as high as 151.769 mg / g at 5.0 min, which is 1.80 times the adsorption capacity of the nanomotor without near-infrared light irradiation (84.242 mg / g). This is because the light-driven Au@DHNTs-DMSA accelerates the adsorption rate and increases the contact probability between Pb(II), making its adsorption capacity higher within a limited time. At the same time, the temperature rise of the solution under near-infrared light irradiation also promotes the improvement of adsorption capacity.

[0073] Test Example 5:

[0074] 8.0 mg of the product Au@DHNTs-DMSA of step (3) in Example 1 was added to a mixed solution (8.0 mL) of K(Ⅰ), Pb(II), Ca(II), Mg(II) and Na(Ⅰ) with an ion concentration of 100 mg / L. The mixture was adsorbed at 25°C for 1.0 h. The supernatant was centrifuged and passed through a membrane. The residual Pb(II) concentration was detected by ICP-OES. The above steps were performed in three groups of parallel experiments. The adsorption capacity Q for different metal ions was calculated using the formula e (mg / g). Figure 8 As shown in (a), in a mixed solution of Ca(Ⅱ), K(Ⅰ), Mg(Ⅱ), Na(Ⅰ) and Pb(Ⅱ) (pH=5.0, 100 mg / L), the adsorption capacity of Au@DHNTs-DMSA for Pb(Ⅱ) is 71.782 mg / g, which is consistent with the adsorption capacity of a single Pb(Ⅱ) solution, and the adsorption capacity for other ions is extremely low, indicating that Au@DHNTs-DMSA has excellent competitive adsorption capacity for Pb(II) with an adsorption efficiency of up to 70%, and has great application potential in blood lead removal.

[0075] Test Example 6:

[0076] Take fresh blood, add PBS solution containing Pb(II) ions, adjust the blood lead concentration to 0.1mg / L, 0.2mg / L, 0.3mg / L and 0.4mg / L, and incubate in a constant temperature water bath at 37℃ for 2.0h to obtain lead-containing blood. Take 2.0mg of the product Au@DHNTs-DMSA of step (3) in Example 1 and add it to 2.0mL of fresh blood with different blood lead concentrations, and irradiate with near-infrared light for 0.5min (to avoid the solution temperature from being too high to damage red blood cells). After adsorption, centrifuge (10000rpm, 10min) to separate the supernatant. Take 0.5mL of the upper solution and add it to a Teflon reactor, then use 4.5mL of a mixture of nitric acid and hydrogen peroxide as the digestion solution (volume ratio of 7:3), digest it at 180℃ high temperature and pressure for 2.0h, then transfer the liquid to a 5.0mL volumetric flask and make up to volume with deionized water. The concentration of Pb(II) in the blood before and after adsorption was determined by ICP-OES. The above steps were carried out in three sets of parallel experiments and blank control experiments, and the adsorption efficiency was calculated. Figure 8 (b) shows the adsorption capacity and removal rate of Au@DHNTs-DMSA in the in vitro blood lead adsorption study. With the increase of blood lead concentration, the adsorption amount and removal rate of blood lead increased. 2 Under near-infrared light irradiation, the maximum blood lead removal rate was 91.25%, which indicates that the nanomotor effectively enhanced the blood lead removal efficiency.

[0077] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a functionalized light-driven nanomotor adsorbent, characterized in that: The following steps are involved: (1) Activation of Halloysite Nanotubes (HNTs): The HNTs powder is dispersed in a hydrochloric acid solution, stirred for a certain period of time at room temperature, and then the HNTs after centrifugal acid treatment are washed with deionized water, and finally dried in a vacuum drying oven to obtain activated HNTs; (2) Halloysite nanotubes loaded with gold nanoparticles Au@HNTs: The HNTs activated in step (1) are mixed with HAuCl4·3H2O, ethanol, toluene, oleylamine and oleic acid, dispersed by ultrasonication, and heated and stirred for the first time under magnetic stirring; Then, a certain amount of ascorbic acid AAc was added, and the mixture was heated and stirred for the second time. The obtained dark product was washed repeatedly with ethanol and toluene alternately for several times, and then washed with toluene for several times to remove the free gold nanoparticles Au NPS in the solution, and finally dried in a vacuum drying oven to obtain the product Au@HNTs; (3) Preparation of Au@DHNTs-DMSA by surface modification of Au@HNTs with polydopamine and DMSA: Au@HNTs were dispersed in Tris buffer, and then mixed evenly with Tris buffer containing dopamine hydrochloride (DA) and dithiothreitol succinic acid (DMSA). After stirring at a certain temperature for a certain time, the solid product was centrifuged and washed with ethanol and deionized water. Finally, it was dried in a vacuum drying oven to obtain the functionalized light-driven nanomotor adsorbent Au@DHNTs-DMSA.

2. The preparation method according to claim 1, characterized in that In step (1), the dosage ratio of the HNTs powder to the hydrochloric acid solution is: 1.0 g: (5.0-15) mL, wherein the concentration of the hydrochloric acid solution is 2.0 mol / L.

3. The preparation method according to claim 1, characterized in that: In step (1), the stirring time is 24 hours; the acid-treated HNTs are washed with deionized water until the solution pH is 7.

0.

4. The preparation method according to claim 1, characterized in that: In step (2), the dosage ratio of the activated NHTs, HAuCl4·3H2O, ethanol, toluene, oleylamine, oleic acid and ascorbic acid (AAc) is 1.0 mg: (1.40-1.50) mg: (0.10-0.15) mL: (0.10-0.15) mL: (0.01-0.05) mL: (0.01-0.05) mL: (5.0-15) mg.

5. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the first heating and stirring is 55° C. and the time is 1.0 min; the temperature of the second heating and stirring is 55° C. and the time is 20 min.

6. The preparation method according to claim 1, characterized in that: In step (3), the dosage ratio of Au@HNTs to Tris buffer containing dopamine hydrochloride (DA) and dithiothiosuccinic acid (DMSA) is 1.0 mg:(0.25-0.75) mL, wherein the concentrations of dopamine hydrochloride (DA) and dithiothiosuccinic acid (DMSA) in the Tris buffer containing dopamine hydrochloride (DA) and dithiothiosuccinic acid (DMSA) are both 2.0 mg / mL.

7. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the Tris buffer is 10 mM, and the pH is 8.

5.

8. The preparation method according to claim 1, characterized in that: In step (3), the stirring temperature is 37° C. and the stirring time is 12 h.

9. The preparation method according to claim 1, characterized in that: In steps (1), (2) and (3), the temperature of the vacuum drying oven is 50°C.

10. Use of the functionalized light-driven nanomotor adsorbent prepared by the preparation method according to any one of claims 1 to 9 for selective adsorption and separation of Pb(II).

Citation Information

Patent Citations

  • Preparation method and application of nano motor adsorbing material

    CN112427009A

  • Near-infrared light-operated Au (at) Cu / H-CeO2 (at) BSA-Cy5 nano motor as well as preparation method and application thereof

    CN114272373A

  • Method for preparing amidoximation hollow mesoporous motor adsorbent based on hard template method and uranium extraction application of amidoximation hollow mesoporous motor adsorbent

    CN116809037A